Study of breast lesions in cytology and its histopathological correlation - S., Rajarajan; P., Balamanikandaraja; P., Visalakshi; M., Anusuya; Nifra, Fathima (International Journal of Research in Medical Sciences, 2023)
Background: Breast cancer is commonly diagnosed malignancy in females and is leading cause of death. Malignant lesions mostly occur after menopause. Fine needle aspiration cytology is minimally invasive technique, used in triple test and produces speedy results. It can able to differentiate between benign and malignant lesions of breast lump. Our study aims to categorize the breast lesion and to correlate FNAC with histopathological studies. Methods: This retrospective study was done in department of pathology from July 2021 to May 2023.107 cases were undergone FNAC and slides were examined and lesions were categorized. Tissue biopsies were obtained, processed and histological sections were made and examined. The FNAC findings were correlated and analyzed with histological findings. Results: Right breast lesions (55%) were more in our study than left breast lesions (42%). Totally 77 cases were diagnosed as benign lesions by FNAC of which 37 cases were biopsied and histological diagnosis of all cases shown as benign category. 6 cases were diagnosed as proliferative breast disease with atypia of which only one case was received for biopsy and diagnosed as atypical ductal hyperplasia. 12 cases were diagnosed as malignancy and 6 biopsies were received with 5 cases were diagnosed as malignant lesions. Sensitivity and Specificity of FNAC in breast lesions were 100% and 97.43% respectively. Conclusions: FNAC is rapid and valuable tool with high sensitivity, specificity and low false positivity. It is useful in preoperative evaluation and avoids unnecessary surgical intervention.